Implementation of Palm Oil Plantation Use Rights in the Dialectic of Investment Certainty and Agrarian Justice - Dinalara Dermawati ButarButar (JURNAL AKTA, 2026)
Hak Guna Usaha (HGU) constitutes a fundamental legal framework governing large-scale palm oil plantations in Indonesia and plays a strategic role in ensuring long-term investment stability. Nevertheless, evolving regulatory schemes, particularly those extending concession periods and lacking explicit landholding limits, have generated tension between economic growth objectives and the constitutional mandate of social justice. Persistent agrarian conflicts, overlapping land claims, and weak recognition of customary and local community rights reveal structural imbalances in the implementation of HGU. This study aims to examine the regulation and practice of HGU within the dialectic of investment certainty and agrarian justice, while proposing a normative reconstruction that strengthens the social function of land. Employing a normative juridical method through statutory, conceptual, and comparative approaches, the research identifies significant disharmony between the Basic Agrarian Law and its derivative regulations. Comparative insights from Malaysia, Brazil, Thailand, and the Philippines demonstrate that clearer landholding limits, smallholder integration, and stronger institutional oversight contribute to a more equitable plantation governance model aligned with constitutional principles.